P-Fuzzy Diffusion Equation Using Rules Base - Jefferson Leite; R. C. Bassanezi; Jackellyne Leite; Moiseis Cecconello (Journal of Applied Mathematics)
We propose a fuzzy system that simulates dispersion of individuals whose movements are described by diffusion. We will use only the position of the population as an input variable for describing the process. We emphasize that the classical diffusion equation along with its analytical solution in no time was used for obtaining our solution.